2022
DOI: 10.1371/journal.pone.0270998
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol brings burdens: A global and continent wise study on alcohol consumption and global burden of diseases

Abstract: This article investigates alcohol consumption attributable burden of diseases. The present study considers the overall effect of Human Development Index (HDI), Socio Demographic Index (SDI) and Gross Domestic Product (GDP) for income to measure how these variables impact Global Burden of Diseases (GDB), bringing a different perspective to the results. Data from over 177 countries mainly including European, Asian, North American, South American, African and Australian regions were analysed from 2000 to 2019. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…While according to National family health survey (NFHS-4) 45% of men in the sample used tobacco in any form and 30% consumed alcohol. 9 While Sivapuram et al estimated at around 8.7% for alcohol abuse and 7.9% for tobacco abuse. 10 Our study revealed that 38.78% participants feel stressed at work place, 56.12% participants do physical exercise.…”
Section: Discussionmentioning
confidence: 98%
“…While according to National family health survey (NFHS-4) 45% of men in the sample used tobacco in any form and 30% consumed alcohol. 9 While Sivapuram et al estimated at around 8.7% for alcohol abuse and 7.9% for tobacco abuse. 10 Our study revealed that 38.78% participants feel stressed at work place, 56.12% participants do physical exercise.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the analysis was conducted using standard robust error eliminating the impact of the heteroscedastic issue. However, past studies further justify that when the sample size is larger the impact of the normality and the collinearity issues are significantly minimised [32][33][34]. Moreover, scatter plot diagrams with linear fit of LPI, GCI and IR were employed to illustrate the country specific trends in the impacts of the control variables on FDI in countries in the African region.…”
Section: Plos Onementioning
confidence: 99%
“…Alcohol and cannabis are among the most frequently used substances and considerably contribute to global burden of disease ( Anthony et al., 2017 ; GBD 2016 Alcohol and Drug Use Collaborators, 2018 ; Jayathilaka et al., 2022 ; Shao et al., 2023 ). Adolescence is a critical period for experimentation and initiation of alcohol and cannabis use in the United States (U.S.) and around the globe.…”
Section: Introductionmentioning
confidence: 99%